Combined effects of a high-fat diet and chronic valproic acid treatment on hepatic steatosis and hepatotoxicity in rats - Zhang Li-fang; Liu Ling-sheng; Chu Xiao-man; Xie Hao; Cao Li-juan; Guo Cen; A Ji-ye; Cao Bei; Li Meng-jie; Wang Guang-ji; Hao Hai-ping (Acta Pharmacologica Sinica, 2016)
Li-fang ZHANG1, #, Ling-sheng LIU1, #, Xiao-man CHU2, Hao XIE1, Li-juan CAO1, Cen GUO1, Ji-ye A1, Bei CAO1, Meng-jie LI1, Guang-ji WANG1, *, Hai-ping HAO1, * 1State Key Laboratory of Natural Medicines, Key Laboratory of Drug Metabolism and Pharmacokinetics, China Pharmaceutical University, Nanjing 210009, China; 2Department of Clinical Pharmacology, Jinling Hospital, Nanjing 210002, China Aim: To investigate the potential interactive effects of a high-fat diet (HFD) and valproic acid (VPA) on hepatic steatosis and hepatotoxicity in rats. Methods: Male SD rats were orally administered VPA (100 or 500 mg·kg-1·d-1) combined with HFD or a standard diet for 8 weeks. Blood and liver samples were analyzed to determine lipid levels and hepatic function biomarkers using commercial kit assays. Low-molecular-weight compounds in serum, urine and bile samples were analyzed using a metabonomic approach based on GC/TOF-MS. Results: HFD alone induced extensive hepatocyte steatosis and edema in rats, while VPA alone did not cause significant liver lesions. VPA significantly aggravated HFD-induced accumulation of liver lipids, and caused additional spotty or piecemeal necrosis, accompanied by moderate infiltration of inflammatory cells in the liver. Metabonomic analysis of serum, urine and bile samples revealed that HFD significantly increased the levels of amino acids, free fatty acids (FFAs) and 3-hydroxy-butanoic acid, whereas VPA markedly decreased the levels of amino acids, FFAs and the intermediate products of the tricarboxylic acid cycle (TCA) compared with the control group. HFD aggravated VPA-induced inhibition on lipid and amino acid metabolism. Conclusion: HFD magnifies VPA-induced impairment of mitochondrial β-oxidation of FFAs and TCA, thereby increases hepatic steatosis and hepatotoxicity. The results suggest the patients receiving VPA treatment should be advised to avoid eating HFD. Keywords: valproic acid; high-fat diet; drug diet interaction; non-alcoholic fatty liver disease; hepatotoxicity; tricarboxylic acid cycle; amino acid; free fatty acid; metabonomics This study was supported by the National Natural Science Foundation of China (Grants 81072695 and 91029746), the National Basic Research Program of China (“973 Program”) (Grant 2011CB505300-03), the Foundation for the Author of National Excellent Doctoral Dissertation of China (Grant 200979); the Natural Science Foundation of Jiangsu Province (Grant BK2010066), and the Program for a New Century Excellent Talent in University (Grant NCET-09-0770). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail hhp_770505@yahoo.com.cn (Hai-ping HAO); guangjiwang@hotmail.com (Guang-ji WANG) Received 2013-06-01 Accepted 2013-08-23